2020
DOI: 10.3390/en13051162
|View full text |Cite
|
Sign up to set email alerts
|

Techno Economic Analysis of Vehicle to Grid (V2G) Integration as Distributed Energy Resources in Indonesia Power System

Abstract: High penetration of electric vehicles (EVs) leads to high stress on a power grid, especially when the supply cannot cover and actively respond to the unpredictable demand caused by charging EVs. In the Java-Madura-Bali (JAMALI) area, Indonesia, the capability of the grid to balance its supply and demand is very limited, and massive EV charging additionally worsens the condition because of unbalanced load profiles. Ancillary services of EVs have led to the idea of utilizing EV batteries for grid support, owing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…For understanding the charging technologies, Table 4 shows the charging power level, charger location, voltage level, maximum power, standard, and charging time. The energy distribution network utilizing EVs-V2G technology-is a promising challenge in the energy sector as the number of EVs increases [107]. Different studies have been conducted to understand the advantages of using these technologies.…”
Section: Charging Timementioning
confidence: 99%
“…For understanding the charging technologies, Table 4 shows the charging power level, charger location, voltage level, maximum power, standard, and charging time. The energy distribution network utilizing EVs-V2G technology-is a promising challenge in the energy sector as the number of EVs increases [107]. Different studies have been conducted to understand the advantages of using these technologies.…”
Section: Charging Timementioning
confidence: 99%
“…This could mean that EV owners not only want to lead green lives or see economic savings in EV use but are also aware of the technology surrounding electromobility. Further analysis of the data revealed that 12 respondents indicated in question (1) that they are interested in electromobility, while in question (10) they gave the answer that they are not familiar with V2G technology. This is a good sign, suggesting that the knowledge about V2X technology is reaching a wider and wider group of people interested in electromobility.…”
Section: Questionmentioning
confidence: 99%
“…It involves voluntarily discharging the battery of an electric vehicle into the power grid or any other facility owned by the end-user, which can be called, in simple terms, a V2G service. It is worth mentioning here that in order to release the full potential of V2G technology, electric vehicles should be integrated with local power systems creating microgrids [10][11][12]. Through the development of renewable energy source (RES) technologies, local energy balancing solutions have become popular and there is certainly a place for electric vehicles in them [13].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other new energy vehicles (such as hybrid electric vehicles), the PEV has larger storage batteries which make the PEV suitable for participate in the vehicle to grid (V2G) or grid to vehicle (G2V) energy management. The technology of V2G/G2V can be used for load leveling and emission reduction [2] [3]. And the V2G/G2V systems are divided into three levels based on charging power level: Level 1 (convenience), Level 2 (primary), and Level 3 (fast) [4].…”
Section: Introductionmentioning
confidence: 99%